2019
DOI: 10.14746/por.2019.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Dystopian and Utopian Omission of Discourse in Three Modern Robinsonades: Lord of the Flies, Concrete Island, The Red Turtle

Abstract: The story of Robinson Crusoe comes to us in the guise of a first-person narrative based in part on a diary. Successor texts have traditionally adopted the same narrative situation, exploiting it in order to foreground ideas of authorship, textual authority and linguistic dominance. This essay pays particularly close attention to those Robinsonades that have not followed this pattern and have instead opted to omit meta-narration and intradiegetic narrator figures. It considers to what ends this is done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This blend of historical and formal research has also been adopted by Jason Pearl (2017) and Rivka Swenson (2020), whose focused readings of Robert Paltock's Peter Wilkins (1750) and Peter Longueville's The Hermit (1727), respectively, have brought these popular 18th‐century Robinsonades back to mainstream 18th‐century criticism. The Robinsonade's formal transformations have also been widely discussed by Patrick Gill, who has studied aspects of intradiegetic narration and omission of discourse in William Golding's Lord of the Flies , J. G. Ballard's Concrete Island and Michael Dudok de Witt's animated film The Red Turtle (2019); the use of counterfactuals in Crusoe , Muriel Spark's Robinson and Yann Martell's The Life of Pi (2020); and issues of textual authority from Defoe to Coetzee's Foe (2021). Approaches like Blaim's or Gill's have shown that while the Robinsonade has gained credibility as a field of critical investigation mostly due to its problematic ideologies, the formal complexity of this tradition merits attention, too.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This blend of historical and formal research has also been adopted by Jason Pearl (2017) and Rivka Swenson (2020), whose focused readings of Robert Paltock's Peter Wilkins (1750) and Peter Longueville's The Hermit (1727), respectively, have brought these popular 18th‐century Robinsonades back to mainstream 18th‐century criticism. The Robinsonade's formal transformations have also been widely discussed by Patrick Gill, who has studied aspects of intradiegetic narration and omission of discourse in William Golding's Lord of the Flies , J. G. Ballard's Concrete Island and Michael Dudok de Witt's animated film The Red Turtle (2019); the use of counterfactuals in Crusoe , Muriel Spark's Robinson and Yann Martell's The Life of Pi (2020); and issues of textual authority from Defoe to Coetzee's Foe (2021). Approaches like Blaim's or Gill's have shown that while the Robinsonade has gained credibility as a field of critical investigation mostly due to its problematic ideologies, the formal complexity of this tradition merits attention, too.…”
mentioning
confidence: 99%
“…Given the technicalities involved, it is only natural that the Screen Age has made much of this variant. While it is no wonder that such box office hits as Cast Away or The Martian have garnered much attention (see also Geriguis, 2020; Pivetti, 2017), the contribution of film studies to the field of Robinsonade criticism lies also in how it has been salvaging relatively obscure examples from critical oblivion (see, for example, Gill, 2019; Gomot, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation